Combined Data Aggregation and Encryption Using Clustered Slepian-Wolf Coding for Wireless Sensor Networks - Pu Wang; Cheng Li; Jun Zheng (IEEE GLOBECOM 2007 - IEEE Global Telecommunications Conference, 2007)
In this paper, we propose a combined data aggregation and encryption scheme using Slepain-Wolf coding for efficient and secured data transmission in wireless sensor networks (WSNs). We first study the optimal intra-cluster rate allocation problem in using Slepain-Wolf coding for data aggregation, which aims to find a rate allocation subject to Slepian-Wolf theorem such that the total energy consumed by all sensor nodes in the cluster for sending encoded data is minimized. Based on the properties of Slepain-Wolf coding with optimal intra-cluster rate allocation, we then propose a novel encryption mechanism, called spatially selective encryption, for data encryption within a single cluster. This encryption mechanism only requires the cluster head to encrypt its data while allowing all cluster members to send their data without performing any encryption. Using this mechanism, as long as the data of the cluster head (or the virtual key ) is protected, the data from all cluster members can also be protected, which can significantly reduce the energy consumption for data encryption. Furthermore, an energy-efficient key establishment protocol is also proposed to securely and efficiently establish the key used for encrypting the visual key .